Total Synthesis of (±) Pimeforazine A and B - Saeed, Shireen Aaisha; Khan, Faiz Ahmed (Synlett, 2025)
Racemic pimeforazine A (1) and B (2), neuroprotective compounds isolated from the weevil Pimelocerus perforatus, have attracted interest due to their potent biological activity. We report the first total synthesis of (±)-pimeforazine A and B, along with 16 structurally related analogues, starting from hydroxytyrosol. The key steps include the in-situ generation of a reactive electrophilic quinone intermediate from hydroxytyrosol, followed by a nucleophilic Michael addition with selected ortho-aminophenols. This one-pot transformation proceeds under mild aqueous conditions, utilizing molecular oxygen as the sole oxidant.
Keywords: Hydroxytyrosol; Biomimetic oxidation; Michael addition; Neuroprotective natural products; Quinone intermediates; Molecular oxygen oxidation